The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1593/tlo.13613
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Nuclear Telomere Organization in Multiple Myeloma

Abstract: Multiple myeloma (MM) is preceded by monoclonal gammopathy of undetermined significance (MGUS). Up to date, it is difficult to predict an individual's time to disease progression and the treatment response. To examine whether the nuclear telomeric architecture will unravel some of these questions, we carried out. Three-dimensional (3D) telomere analysis on samples from patients diagnosed with MGUS and MM, as well as from patients who went into relapse. Telomere signal intensity, number of telomere aggregates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 74 publications
3
24
0
Order By: Relevance
“…In comparison, normal lymphocyte nuclei had a smaller, rounder shape and emitted a brighter DAPI signal than myeloma nuclei [Klewes et al, 2013]. In this study, we have identified myeloma and lymphocyte nuclei based on size and intensity of the DAPI staining.…”
Section: Methodsmentioning
confidence: 79%
“…In comparison, normal lymphocyte nuclei had a smaller, rounder shape and emitted a brighter DAPI signal than myeloma nuclei [Klewes et al, 2013]. In this study, we have identified myeloma and lymphocyte nuclei based on size and intensity of the DAPI staining.…”
Section: Methodsmentioning
confidence: 79%
“…White blood cells were isolated as previously described . Briefly, 10 ml peripheral blood from each patient was collected in EDTA‐treated tubes.…”
Section: Methodsmentioning
confidence: 99%
“…White blood cells were isolated as previously described. 44 Briefly, 10 ml peripheral blood from each patient was collected in EDTA-treated tubes. Mononuclear cells were separated using Ficoll-Paque (GE Healthcare Life Sciences, Quebec, Canada) by a 30 min centrifugation at 200g.…”
Section: Isolation Of Lymphocytes and Myeloma Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equipped with such software, we have measured the 3D organization of telomeres in multiple cancers including HL, multiple myeloma, myelodysplastic syndromes and acute myeloid leukemia, glioblastoma, neuroblastoma, and prostate cancer [48][49][50][51][52][53] ( Figure 7). Nuclear genome changes do not only occur in cancer.…”
Section: Telomeresmentioning
confidence: 99%